The Effects of Calorie Restriction and Exercise on Age-Related Alterations in Corpus Cavernosum - ŞENER, GÖKSEL (FRONTIERS MEDIA SA, 2020)
Background Aging is an important risk factor for erectile dysfunction (ED). Both calorie restriction (CR) and physical exercise (PE) have been established as a non-medical method for the improvement of detrimental changes in aging. It is well documented that both CR and PE influence on sympathetic and parasympathetic systems; however, there are few studies on non-adrenergic non-cholinergic pathways. This study aims to investigate the NO-mediated mechanisms of CR and PE on corpus cavernosum in aged rats. Materials and Methods 3 and 15 month-old rats were divided into five experimental groups: young rats fed ad libitum (Y-C), aged rats fed ad libitum (O-S), aged rats with CR (O-CR), aged rats with PE (O-PE), and aged rats with CR and PE (O-CR-PE). CR was applied to animals as a 40% reduction of daily food intake for 6 weeks. PE was moderate swimming at 30 min at 3 days/week. The effects of CR and PE were evaluated by histologic, biologic, and in-vitro tissue bath studies. Results The outcomes in CR and PE groups (characterized by decreased nitrosative damage together with increased antioxidant capacity) were improved in comparison to the O-S. Apoptotic biomarkers were also lower and both endothelial and smooth muscle cell' functions were preserved too. There was no statistical difference between apoptosis, antioxidant capacity, and nitrosative damage parameters. Contractile responses to phenylephrine and relaxation responses to carbachol were: O-CR > O-PE > O-CR-PE. In these groups, NOS protein levels determined by western-blot were: eNOS: O-CR = O-CR + PE > O-PE; iNOS: O-CR = O-PE > O-CR-PE; nNOS: O-PE > O-CR-PE > O-CR. Conclusion In our study, both CR and PE prevented age-related changes in the corpus cavernosum of rats. Reducing nitrosative damage in the neurovascular structure was the main mechanism. CR and exercise restored the endothelial and smooth muscle cells in corpus cavernosum by decreasing apoptosis. The mechanism of enhancing functional response in corpus cavernosum with CR was the improvement of endothelial function via eNOS activation however it involves increases in the NO-cGMP signaling pathway by an endothelium-independent mechanism with PE. This might be a direct stimulation of smooth muscle cells by NO, which released from the cavernous nerve endings via nNOS activation.
Keywords: erectil dysfunction; calorie restriction; physical exercise; aging; nitric oxide; IMPROVES ERECTILE FUNCTION; NITRIC-OXIDE SYNTHASE; OXIDATIVE STRESS; DYSFUNCTION; MECHANISMS; SOD